2011
DOI: 10.1097/qai.0b013e318207a55b
|View full text |Cite
|
Sign up to set email alerts
|

Survival of HIV-Infected Children: A Cohort Study From the Asia-Pacific Region

Abstract: Background Combination antiretroviral therapy (ART) has been used for HIV-infected children in many Asian countries since 2002. This study describes survival outcomes among HIV-infected children in a multicenter regional cohort in Asia. Patients and Methods Retrospective and prospective data collected through March 2009 from children in five countries enrolled in TREAT Asia's Pediatric HIV Observational Database (TApHOD) were analysed. Multivariate Cox proportional hazard models were used to assess factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 23 publications
9
33
4
3
Order By: Relevance
“…A study by Brady et al (2010), Lumbiganon et al (2011) and Phongsamart et al (2013) reported that HIVinfected children with low baseline CD4 cell counts had a strong likelihood of early mortality. The results in this current study are also consistent with the findings in the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Brady et al (2010), Lumbiganon et al (2011) and Phongsamart et al (2013) reported that HIVinfected children with low baseline CD4 cell counts had a strong likelihood of early mortality. The results in this current study are also consistent with the findings in the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of children in antiretroviral treatment (ART) era has dramatically improved in both resource-rich and resource-limited settings [8-12]. Although coverage with ART is improving, it is estimated that in low and middle income countries only around 34% of children aged <15 years needing ART are estimated to be receiving treatment, compared with 68% in adults [2,7,13].…”
Section: Children and Hivmentioning
confidence: 99%
“…A study in [11] was found that those children with WHO clinical stage IV had an increased risk of death. Similar to our finding, studies by [13,14,15] ART at Gondar University Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mortality among these high risk groups contributed to the higher rate of mortality. A study in [10,11,12] reported that patients with low baseline CD4 cell count were a strong risk factor for early mortality of HIV-infected children. Our results are also consistent with the findings in the above studies.…”
Section: Discussionmentioning
confidence: 99%